When and how aesthetics influences financial decisions - Townsend, Claudia; Shu, Suzanne B. (Journal of Consumer Psychology, 2010)
AbstractWe observe the influence of aesthetic design on consumer behavior involving financial products—an area where financial decision‐makers say they do not take aesthetics into account. In a series of three studies we find that the look of a document in hypothetical investment decisions impacts stock valuation and behavior in some but not all situations. Specifically, our results show that calling attention to the influence of design on behavior moderates the effect, including the paradoxical finding that the effect of design is attenuated when investments involve entities for which aesthetics is of intrinsic value.